STRATEGI PEMASARAN IKLAN PADA RADIO MUARA PARANTI 105,6 FM PANDEGLANG BANTEN - Marwati Marwati (Jurnal Komunikasi dan Media, 2026)
Radio is an electronic medium that has existed for a long time and continues to endure to this day. Despite the emergence of numerous other information and entertainment platforms driven by increasingly advanced technology, radio still retains a loyal audience. It remains an affordable, practical source of entertainment and information that can be listened to anytime and anywhere.The objective of this research is to identify the advertising marketing strategy used by Muara Paranti Radio 105.6 FM in Pandeglang, Banten. This study employs a qualitative approach using a descriptive method, which involves several steps: data collection, data organization, data presentation, and drawing conclusions.The results of this study show that, in its advertising marketing strategy, Radio Paranti uses the Three Ways Strategy.First is the pull strategy, which aims to attract advertisers to place their product advertisements on Radio Paranti. This is done by sending out the radio’s company profile along with an offer that does not initially include pricing information.Second is the push strategy, which seeks to turn that initial interest into a desire to collaborate. In this stage, the advertiser is allowed to propose or negotiate the advertising rate.Finally, the pass strategy is used to build a positive public opinion among the community, including potential advertisers.